Authentic Materials for Integrated Skills at Mechanical Engineering Students - Sari, Farnia; Nurulanningsih; Amaliah; Wahyudi, Agus; Sulistyo, Bambang (Universitas Jambi, Indonesia, 2024)
English for Specific Purposes (ESP) is one of the obligatory courses in universities, and all undergraduate students are required to pass these courses. The main aim of ESP courses is to enhance students' knowledge to meet their academic requirements and future career needs in the global trend. This research used a mixed-method design that integrated both quantitative and qualitative data. Furthermore, the researchers used observations, questionnaires, and interviews to collect the data. The results of the students' need assessment about authentic materials were obtained through interviews with experts and stakeholders from academic institutions. In addition, the data showed that students required authentic materials, stakeholders supported their learning activities to enhance their communicative competence in English skills, and experts had positive responses toward using authentic materials for teaching ESP courses.